The relationship between decision-making uncertainty and information integration in FMCG supply chains. - Xue, Yufei (Cranfield University, 2023)
The relationship between decision-making uncertainty and information integration is important for supply chain stakeholders. However, the detailed interactions in this relationship have received limited explanation. This study empirically identifies the key factors in the relationship and investigates their interactions. Based on three papers, the thesis captures the relationships and interactions between decision-making uncertainty and information integration, offering empirical evidence on the nature of these relationships. The first paper develops a theory-based relational framework for the relationship between decision-making uncertainty and information integration. A systematic literature review (SLR) approach is conducted, and 86 articles published between 2001–2022 are reviewed. The findings support the concept of fit in information processing theory (IPT), demonstrating that information processing needs and capabilities must match to positively impact supply chain performance. The paper also indicates that the high level of environmental and industry uncertainty in decision-making uncertainty increases supply chain stakeholders’ willingness to implement information integration. Simultaneously, supply chain stakeholders implement Industry 4.0 information and communication technologies (ICTs) to support technology-based information integration and to reduce the impact of decision-making uncertainty in the supply chain. The relationship between decision-making uncertainty and information integration has also been shown to impact supply chain performance. The second paper uses the Internet of Things (IoT) to represent ICTs in Industry 4.0. The study conducted a multiple-case study in the fast fashion industry in China to investigate the relationship between decision-making uncertainty and information integration affected by the implementation of the IoT. Consequently, environmental complexity, richness, and the bullwhip effect are identified as the key factors in decision-making uncertainty; information accuracy, quality, efficiency, and security are identified as the key factors in information integration; and management cost and asset utilisation in supply chain costs, alongside response speed, product flexibility, and efficiency in production operations, are identified as supply chain performance. Moreover, the findings highlight that the alignment between decision-making uncertainty and information integration is important and consists of several interactions among environmental complexity, environmental richness, the bullwhip effect, and information accuracy, quality, and efficiency. This research elaborates on the theory-based relational framework developed in Paper 1 and it provides empirical support to several conceptual studies on implementing IoT applications. The third paper assesses the interactions identified in Paper 2 and their impact on supply chain performance. After analysing the data collected from the supply chain stakeholders of the fast fashion industry in China through structural equation modelling (SEM), the analysis results confirm the importance of key factors in decision-making uncertainty (environmental complexity, environmental richness, and bullwhip effect) and IoT-based information integration (information quality, information accuracy, and information efficiency). The interactions between information accuracy and environmental complexity, information accuracy and environmental richness, information quality and the bullwhip effect, and information efficiency and the bullwhip effect are identified as the key interactions in the alignment between decision-making uncertainty and information integration. The study also emphasises decision-making uncertainty’s direct impact on supply chain performance. It concludes that the interactions between decision-making uncertainty and IoT-based information integration partially mediate the relationship. This paper is the first empirical study to explain the detailed interactions between information integration and decision- making uncertainty, and it provides empirical evidence for theoretical associations.
Ghadge, Abhijeet - Associate Supervisor
Keywords: Internet of Things; Information integration; Decision-making uncertainty; Supply chain performance; Information processing theory; relationships